Digital Marketing Brand Awareness Strategy for Retail Sales Acceleration Strategi Kesadaran Merek Pemasaran Digital untuk Akselerasi Penjualan Ritel: Strategi Kesadaran Merek Pemasaran Digital untuk Akselerasi Penjualan Ritel - Siti Marwah; istian kriya almanfaluti (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid evolution of social media platforms has transformed commercial communication, requiring businesses to adapt their promotional frameworks to maintain relevance. Specific Background: PT Alkahfi Supply Chain, an importer of household and electrical goods, faces the challenge of penetrating the highly competitive local consumer market. Knowledge Gap: While the theoretical benefits of online promotion are recognized, there is limited operational understanding of how targeted content optimization on platforms like TikTok and Shopee specifically converts visibility into tangible sales within the imported goods supply chain sector. Aims: This study seeks to formulate and evaluate a comprehensive digital marketing strategy aimed at maximizing brand awareness and stimulating retail sales for PT Alkahfi Supply Chain. Results: Using descriptive qualitative analysis of e-commerce metrics and social media engagement data, the research reveals that consistent, high-quality content integrated with competitive pricing significantly elevates consumer interest; however, current conversion rates indicate a need for improved interactive features and targeted promotional discounts. Novelty: This study provides a granular assessment of social commerce metrics (such as Gross Merchandise Value distribution and specific product trend analysis) linked directly to inventory management within a non-restricted import supply chain. Implications: Enterprises should prioritize dynamic content creation, proactive customer engagement strategies, and data-driven inventory selection on digital platforms to foster brand loyalty and ensure sustainable market profitability. Highlights: Strategic optimization of e-commerce product displays directly correlates with improved consumer conversion rates. Integrating social media engagement with localized supply chain operations strengthens retail market positioning. Discount-driven promotional tactics remain essential for accelerating inventory turnover in competitive digital marketplaces. Keywords: Brand Awareness, Digital Marketing, Supply Chain Management, E-commerce Strategy, Consumer Engagement